2017
DOI: 10.1093/neuonc/nox036.404
|View full text |Cite
|
Sign up to set email alerts
|

P14.19 Preclinical and clinical efficacy of entrectinib in primary and metastatic brain tumors harboring NTRK, ROS1, or ALK gene fusions

Abstract: Abstractsiii106 NEURO-ONCOLOGY • MAY 2017 age, KPS, EGFR and ALK status. Clinical outcome was evaluated by neurological examination and MRI at 2 months after RT and then every 3 months. RESULTS: From June 2009 to December 2015, 156 patients for 228 BMs treated were included in this evaluation. Fifty (32.1%) were female and 106 (67.9%) male with a median age of 62 years (range 27-93 years). The greater number of patients had a KPS 90-100, were in RPA class II, had DS-GPA score 2.5-3, and had 1-2 BMs (88.4%).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…In addition, and consistent with these relative AP-ER values, entrectinib (despite not reaching steady state) showed a more favourable CSF-to-plasma unbound concentration ratio than crizotinib and larotrectinib (both of which reached steady state) following constant intravenous infusion for 4-6 h in an in vivo brain distribution study (> 0.2 vs ≈ 0.03 and ≈ 0.03) [11]. Entrectinib demonstrated CNS penetration [5,11] (e.g. steady-state brain/plasma ratios of 1.4-2.2, 0.6-1.0 and 0.4 following repeated daily oral administration in dog, rat and mouse, respectively [5]) and inhibited tumour growth and improved survival in murine models intracranially injected with human tumour cell lines driven by an NTRK [11] or ALK [24] fusion.…”
Section: Pharmacodynamic Properties Of Entrectinibsupporting
confidence: 59%
See 1 more Smart Citation
“…In addition, and consistent with these relative AP-ER values, entrectinib (despite not reaching steady state) showed a more favourable CSF-to-plasma unbound concentration ratio than crizotinib and larotrectinib (both of which reached steady state) following constant intravenous infusion for 4-6 h in an in vivo brain distribution study (> 0.2 vs ≈ 0.03 and ≈ 0.03) [11]. Entrectinib demonstrated CNS penetration [5,11] (e.g. steady-state brain/plasma ratios of 1.4-2.2, 0.6-1.0 and 0.4 following repeated daily oral administration in dog, rat and mouse, respectively [5]) and inhibited tumour growth and improved survival in murine models intracranially injected with human tumour cell lines driven by an NTRK [11] or ALK [24] fusion.…”
Section: Pharmacodynamic Properties Of Entrectinibsupporting
confidence: 59%
“…The diagnosis and treatment of solid tumours has firmly entered the era of personalized (or precision) medicine, with optimal patient management requiring molecular profiling aimed at identifying oncogenic driver mutations that are actionable or potential therapeutic targets [1][2][3][4]. In this regard, gene rearrangements (fusions) involving the neurotrophic tyrosine receptor kinase (NTRK) genes NTRK1, NTRK2 and NTRK3 [encoding the tropomyosin receptor kinase (TRK) receptors TRKA, TRKB and TRKC, respectively], the c-ros oncogene 1 receptor tyrosine kinase (ROS1) gene [encoding proto-oncogene tyrosine-protein kinase ROS (ROS1)] and the anaplastic lymphoma kinase gene (ALK; encoding the ALK receptor tyrosine kinase) are variously implicated, albeit often infrequently, in a broad range of (> 40) solid tumour types [5]. NTRK fusions, which are thought to be present in up to 1% of all solid tumours, are found in a wide variety of adult and paediatric tumour types; they are extremely common (incidence > 90%) in rare cancer types, such as infantile fibrosarcoma and mammary analogue secretory carcinoma (MASC), but rare (incidence predominantly < 1%) in more common cancer types, such as lung, breast and colorectal cancers, and melanomas [2,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Intratumoral target engagement remains one major obstacle for effective treatment of brain tumors, which are considered to be protected from anticancer drugs by the BBB. Entrectinib demonstrated CNS penetration capacity in preclinical models with repeated oral daily dosing [ 26 , 50 ]. In our study, we could demonstrate CSF penetrance of entrectinib in a patient for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…148,149 There were patients with glioblastoma on those trials, and subgroup analyses suggested a benefit from NTRK inhibitors in these patients. 150,151 There are also numerous FGFR TKIs in development, and there are documented cases of response. 152 Although many trials of targeted therapies to date have not demonstrated significant efficacy, better enrichment strategies using precision biomarkers will increase the chances of future success.…”
Section: Precision Oncology and Targeted Therapymentioning
confidence: 99%